Preparation Of Paper For 2nd ICEL 2014 The Effectiveness Of Using Cooperative Learning Type Number Heads Together (NHT) Improving Reading Comprehansion Of The Students At SMP N 20 Tangerang - Destiani Rahmawati (STAI Asy-Syukriyyah, 2014)
The teacher found some constraints in students of understanding English text such as limited vocabulary, the students are lack of stock of the words, the students who have little knowledge of vocabulary will face some difficulties to understand the written language. The students’ lack knowledge about the text, when student have lack knowledge about the topic that make student difficult to conclude the idea of the text, they are hard to understand what the text tells about. This research used Experimental design. The writer teaches two different classes. They are control and experimental class. The population of this research is 305 students eighth grade in Junior High School which consist of eight classes. The writer used cluster random sampling technique to measure the reading comprehension test. In collecting data, the writer will give reading comprehension tests to the students using multiple choice, and questioner in teaching learning using NHT in reading comprehension. The test is given to get the objective data of student’s achivement in reading comprehension by using cooperative learning type NHT in experimental class. The writer will apply two test: there is pre test and post test. The results data of analysis pre-test of the experimental class and the control class show there is no difference in mean, where value of the average values experiment class is 46.1 while the average control class is 43,1 after the experiment class was given treatment, turned out to give effect to the post-test score. The analysis data of post-test that have been done, it shows that there are differences in the average value of post-test between the experiment class and the control class, where the average in the experiment class is 68 while the control class average is 61.7. Based on the data analysis of post-test, it shows that values tcount more than ttable, where tcount is 2.18 while ttable is 1.99, so hypothesis statistic (H1) is accepted. This suggests that the cooperative learning type NHT more effective than conventional learning. Based on those results, it can be concluded that the application of cooperative learning type NHT technique is effective in teaching reading comprehension